Prognostic factors in patients with advanced non-small cell lung cancer after long-term Anti-PD-1 therapy (HOT1902). (June 2021) - Ito, Shotaro; Asahina, Hajime; Honjo, Osamu; Tanaka, Hisashi; Honda, Ryoichi; Oizumi, Satoshi; Nakamura, Keiichi; Takamura, Kei; Hommura, Fumihiro; Kawai, Yasutaka; Ito, Kenichiro; Sukoh, Noriaki; et al.
Highlights: Data of 676 advanced NSCLC patients treated with ICI were analyzed. The efficacy and safety of long-term ICI treatment in the real world were studied. Rechallenge treatment of ICI was not effective in this study. Smoking and complete response were related to better PFS in the long-term treatment. Abstract: Objectives: Limited information is available on the appropriate treatment duration of immune checkpoint inhibitors (ICIs). We aimed to identify candidates who would benefit from ICI discontinuation after one year of treatment for metastatic non-small cell lung cancer (NSCLC). Materials and methods: This retrospective multi-institutional observational study examined medical records of all consecutive patients with advanced or recurrent NSCLC, who started ICI monotherapy at 15 institutions in Japan between December 2015 and December 2017. Patients who received initial ICI therapy for >1 year without progressive disease were defined as the long-term treatment (LT) group; others were defined as the non-long-term treatment (NLT) group. Primary outcomes included the prognostic factors in the LT group, whereas secondary outcomes included efficacy of ICI rechallenge, safety, and survival outcomes in the overall population. Results: In total, 676 patients were enrolled, and 114 (16.9 %) were assigned to the LT group. The median time interval from the start of initial ICI administration to data cutoff was 34.3 months (range, 24.1–47.8); thus, all surviving patients were followed-up for at least 2 years from the start of initial ICI. Median progression-free survival (PFS) was longer in the LT than in the NLT group (33.6 months vs. 2.7 months; p < 0.001). On multivariate analysis, significantly better PFS was associated with smoking (hazard ratio [HR]=0.36, p = 0.04), and complete response (CR; HR=uncomputable, p < 0.001) in the LT group. Thirty-seven patients (5.5 %) received ICI rechallenge, including 10 in the LT group. Among patients receiving rechallenge treatment, the median PFS was 2.2 months, with no difference between the LT and NLT groups. Conclusions: In the LT group, smoking and achieving CR were significantly associated with better PFS. Since rechallenge treatment was not effective, careful consideration is required for discontinuing ICI. However, these prognostic factors are helpful in considering candidates for ICI discontinuation. Trial Registration: UMIN ID, UMIN000041403